Karyotype evolution and phylogenetic analyses in the genus Cardiospermum L. (Paullinieae, Sapindaceae) - Urdampilleta, Juan Domingo (2012)
Cardiospermum L. belongs to the Paullinieae tribe (Sapindaceae) and comprises 16 species. Of these, 12 species are present in South America and all occur in Brazil. Cardiospermum shows the most variable chromosome number of the tribe. Phylogenetic relationships within the genus Cardiospermum, especially with other species of the tribe, are poorly understood. This research focuses on characterisation of the karyotypic features of Cardiospermum using conventional cytogenetic methods, CMA/DAPI chromosome banding and fluorescence in situ hybridisation (FISH). To elucidate the phylogeny of the genus, the nuclear markers ITS1 and ITS2 were sequenced and analysed using maximum parsimony and Bayesian inference. Cardiospermum shows important diversity in basic numbers, with x = 7, 9, 10, 11 and 12. All species studied have metacentric and submetacentric chromosomes, some species have subtelocentric chromosomes, while telocentric chromosomes are absent. The interphase nuclei differentiate the Cardiospermum species into two groups. The CMA3/DAPI chromosome banding revealed the presence of an AT-rich terminal region in C. corindum, C. grandiflorum and C. urvilleoides, whereas GC-rich regions were found in C. grandiflorum, C. halicacabum var. halicacabum, C. halicacabum var. microcarpum, C. heringeri and C. integerrimum. FISH revealed syntenic and non-syntenic distribution of the 18-5.8- 26S and 5S rDNA. The syntenic distribution always occurred in the short arms of the same chromosome in all of the species. The phylogenetic relationships reveal, in part, the taxonomic arrangement of the genus Cardiospermum.